BRIDGING TECHNOLOGY AND SUSTAINABILITY: EMPIRICAL INSIGHTS INTO GREEN FINTECH-DRIVEN ACCOUNTING PRACTICES - Arofah, Triani; Ramadhanti, Wita; Rusmana, Oman (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study examines the role of Green Financial Technology (Green Fintech) in promoting sustainable accounting practices among publicly listed companies in Indonesia. Using a quantitative approach with secondary data from sustainability reports and ESG disclosures, the study evaluates the impact of Green Fintech adoption on corporate transparency and environmental performance. The analysis reveals that the integration of digital financial solutions—such as green investment platforms, ecological data analytics, and blockchain-based reporting—contributes significantly to improving ESG performance, carbon disclosure, and the adoption of circular economy practices. Furthermore, stakeholder engagement mediates the relationship between Green Fintech and firm performance, while the implementation of circular economy principles strengthens this link. This research contributes to the growing body of literature on sustainable accounting by presenting an empirical model that highlights the strategic value of digital environmental innovation. The findings offer practical implications for corporate managers, regulators, and Fintech developers seeking to enhance sustainable value creation in emerging economies.